2021
DOI: 10.3389/fcimb.2021.694395
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Autoinducer-2 Rescues Intestinal Dysbiosis and Intestinal Inflammation in a Neonatal Mouse Necrotizing Enterocolitis Model

Abstract: Autoinducer-2 (AI-2) is believed to be a bacterial interspecies signaling molecule that plays an important role in the regulation of the physiological behaviors of bacteria. The effect of AI-2 on the process of necrotizing enterocolitis (NEC) is unknown, and the aim of this study was to study the effect of AI-2 in a mouse NEC model. C57BL/6 mouse pups were randomly divided into three groups: the control group, the NEC group, and the NEC+AI-2 (NA) group. Exogenous AI-2 (500 nM) was added to the formula milk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Similarly, the abundance of Clostridium_sensu_stricto_1 in PG was also high (Fig. 2b), which was similar to those reports that its abundance increases signi cantly when the intestinal microorganisms are out of imbalance [42,43]. It is speculated that lung in ammation may affect the composition of intestinal microorganisms.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, the abundance of Clostridium_sensu_stricto_1 in PG was also high (Fig. 2b), which was similar to those reports that its abundance increases signi cantly when the intestinal microorganisms are out of imbalance [42,43]. It is speculated that lung in ammation may affect the composition of intestinal microorganisms.…”
Section: Discussionsupporting
confidence: 87%
“…The relative abundance of Clostridium_sensu _stricto_1 was significantly increased in the gut microecological imbalance. Ji et al [ 31 ] found significant enrichment of Clostridium_sensu_stricto_1 in a model of necrotic enterocolitis in neonatal mice. It was also found to be significantly enriched in IBS syndrome [ 32 ] and leukemia [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proin ammatory cytokines TNF-α, IL-1β, and IL-6 were elevated in infants and animal models with NEC (45,46), which can be suppressed by the use of TLR4 inhibitors (8, 47). Our experiment showed that early supplement with β-glucan reduced TLR4 and NF-κB protein expression levels in NEC mice.…”
Section: Discussionmentioning
confidence: 99%